Strategi Pengembangan Karir Sumber Daya Manusia Dalam Dunia Kerja - Nonius Apriliano; Fatkhur Rizka Azizur Rahman; Fahmi Idris; Fatchul Asy'ari; Fathur Rozy (Lembaga Pengembangan Kinerja Dosen, 2024)
Career development for human resources (HR) is a crucial aspect in the modern world of work. With increasing global competition and rapid technological change, organizations need to ensure that their employees have the skills and knowledge necessary to face the challenges of the future. Career development for human resources (HR) is a crucial aspect in the modern world of work. The aim of writing this article is to provide a comprehensive understanding of human resources (HR) career development strategies in the modern world of work. The method used in writing this article is to collect references from national and international journals via Google Scholar and summarize so that you can draw up conclusions. The results and discussion show that career development for human resources (HR) is a crucial aspect in the modern world of work. With increasing global competition and rapid technological change, organizations need to ensure that their employees have the skills and knowledge necessary to face the challenges of the future. The strategies used are competency assessment, training and development, mentoring and coaching, employee empowerment, as well as job rotation and enrichment. The conclusion of this article is that with strategies such as competency assessment, training and development, mentoring and coaching, employee empowerment, as well as job rotation and enrichment, organizations can ensure that their employees are ready to face future challenges and reach their maximum potential. Through a holistic and planned approach, career development not only